One Good Turn Deserves Another - Barbieri, William A., Jr (Journal of religious ethics, 2017)
Elizabeth Bucar has provided a service to the guild with her introduction to the emergent field of visual ethics. In this comment I undertake to expand the picture she presents. I argue that the visual dimension of ethics includes a dark side not addressed in her piece, and go on to consider a number of current avenues of inquiry in which religious ethics intersects with visual studies. After briefly considering some of the distinctive methodological challenges attending the visual turn in ethics, I conclude my survey of this new field with some comments on the moral qualities of cinema.